Synthesis and Characterization of Nano-TiO2/SiO2-Acrylic Composite Resin - Bin Du; Feng Chen; Rubai Luo; Shisheng Zhou; Zhengneng Wu (Advances in Materials Science and Engineering)
Waterborne acrylic resin is widely used as a binder of waterborne printing ink because of its excellent comprehensive properties. However, its further developments and applications are hindered by its poor UV resistance and water resistance. Therefore, an approach to prepare acrylic resin with excellent UV resistance and water resistance is described in this present study. The nano-TiO2/SiO2 composite particles were first modified with a silane coupling agent (KH-570) and a titanate coupling agent (NDZ-101) and then embedded into acrylic resin via a blending method. Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and thermogravimetry analysis (TGA) were applied to investigate the structure and morphology of the modified nano-TiO2/SiO2 composite particles. The effects of the modified nano-TiO2/SiO2 composite particles on the UV and water resistance of the acrylic resin were investigated by UV spectroscopy and water resistance analysis. The weight loss of modified nano-TiO2/SiO2 was about 20% when heated to 600°C, which indicated that the nano-TiO2/SiO2 composite particles were modified by the coupling agents successfully. The UV-Vis spectra of acrylic resin showed that the UV resistance was improved upon the addition of nano-TiO2/SiO2. The water absorption of the nano-TiO2/SiO2-acrylic resin was less than 5%, indicating that the water resistance of the material was improved.